2009
DOI: 10.1093/pcp/pcp030
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Molecular Ecology of Herbivore-Induced Plant Volatiles: Proximate Factors and Their Ultimate Functions

Abstract: In response to herbivory, plants emit specific blends of herbivore-induced plant volatiles (HIPVs). HIPVs mediate sizable arrays of interactions between plants and arthropods, microorganisms, undamaged neighboring plants or undamaged sites within the plant in various ecosystems. HIPV profiles vary according to the plant and herbivore species, and the developmental stages and conditions of the live plants and herbivores. To understand the regulatory mechanisms underling HIPV biosynthesis, the following issues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
375
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(386 citation statements)
references
References 96 publications
4
375
0
7
Order By: Relevance
“…Hopke et al 1994;Ozawa et al 2000;Arimura et al 2009). For example, Hopke et al (1994) found that treating lima bean (Phaseolus lunatus L.; Fabaceae) with JA increased the emission of volatiles similar to the HIPVs released by leaves infested with either two-spotted spider mites (TSSMs), Tetranychus urticae C.L.…”
Section: Introductionmentioning
confidence: 99%
“…Hopke et al 1994;Ozawa et al 2000;Arimura et al 2009). For example, Hopke et al (1994) found that treating lima bean (Phaseolus lunatus L.; Fabaceae) with JA increased the emission of volatiles similar to the HIPVs released by leaves infested with either two-spotted spider mites (TSSMs), Tetranychus urticae C.L.…”
Section: Introductionmentioning
confidence: 99%
“…The emission of (E)-β-ocimene, which is typically induced by abiotic stress, is increased proportionally with the soil salinity. (E)-beta-ocimene is synthesized in the plastid via the 2-C-methyl-d-erythritol-4-P pathway [38] and its emission could be due to changes in metabolite channeling. In the same way, the 2-carene and beta-phellandrene emissions increased with the concentration of soil salinity ( Figure 5).…”
Section: The Influence Of Soil Salinity On Volatile Organic Compoundsmentioning
confidence: 99%
“…Takabayashi and Dicke 1996; Arimura et al 2009). Most of the previously reported studies on the ecological function of HIPVs focused on a single tritrophic system in which one herbivores of one species attacked an individual plant.…”
Section: Introductionmentioning
confidence: 99%